2024
DOI: 10.3390/biomedicines12010232
|View full text |Cite
|
Sign up to set email alerts
|

Novel Serum Biomarkers for Patients with Allergic Asthma Phenotype

Jolita Palacionyte,
Andrius Januskevicius,
Egle Vasyle
et al.

Abstract: In distinguishing the allergic asthma (AA) phenotype, it has been identified that specific biomarkers could assist; however, none of them are considered ideal. This study aimed to analyze three groups of biologically active substances in the serum. Twenty steroid-free AA patients, sensitized to Dermatophagoides pteronyssinus, and sixteen healthy subjects (HSs) were enrolled in this study. Blood samples were collected from all patients. Additionally, all AA patients underwent a bronchial allergen challenge (BAC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…41 It has been shown that miRNAs in exosomes is a key intercellular messenger in lung that can serve as a regulator of intercellular communication, mediates of immune, untimely promoting the progression of asthma. 42,43 In this study, we have found that the expression of hsa-miR-155-5p in AEC-Exos significantly increased after exposure to HDM stress and RSV infection, leading to the activation of T cells and the enhanced differentiation of Th2 cells. Elevated levels of hsa-miR-155-5p were also observed in the lungs of mice experiencing acute asthma exacerbation.…”
Section: Discussionmentioning
confidence: 67%
“…41 It has been shown that miRNAs in exosomes is a key intercellular messenger in lung that can serve as a regulator of intercellular communication, mediates of immune, untimely promoting the progression of asthma. 42,43 In this study, we have found that the expression of hsa-miR-155-5p in AEC-Exos significantly increased after exposure to HDM stress and RSV infection, leading to the activation of T cells and the enhanced differentiation of Th2 cells. Elevated levels of hsa-miR-155-5p were also observed in the lungs of mice experiencing acute asthma exacerbation.…”
Section: Discussionmentioning
confidence: 67%
“…A deeper understanding and identification of specific phenotypes and endotypes of asthma may lead to the development of tailored therapeutic interventions, potentially improving asthma management and patient care [ 56 , 71 , 72 , 73 , 74 , 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…A handheld Vivatomo-me device (Bosch Healthcare Solutions, Waiblingen, Germany) was used for the aforementioned FeNO analysis, with measurements produced according to the manufacturer's instructions. The details and techniques employed for the performance of this procedure are described in [15].…”
Section: Fractional Exhaled Nitric Oxide (Feno) Testmentioning
confidence: 99%
“…During processing, the samples were rigorously controlled and monitored. More detail on the description technique used can be found in [15].…”
Section: Complete Blood Count and Igementioning
confidence: 99%